2015
DOI: 10.1007/s10071-015-0872-2
|View full text |Cite|
|
Sign up to set email alerts
|

Rats demonstrate helping behavior toward a soaked conspecific

Abstract: Helping behavior is a prosocial behavior whereby an individual helps another irrespective of disadvantages to him or herself. In the present study, we examined whether rats would help distressed, conspecific rats that had been soaked with water. In Experiment 1, rats quickly learned to liberate a soaked cagemate from the water area by opening the door to allow the trapped rat into a safe area. Additional tests showed that the presentation of a distressed cagemate was necessary to induce rapid door-opening beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
210
5
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(236 citation statements)
references
References 33 publications
16
210
5
5
Order By: Relevance
“…This was further attributed to social contact but again it poses the possibility that social contact was empathic in nature. Assuming that the social contact explanation was true, rats will be motivated to open restrainers and trap doors for distressed and non-distress cagemates indiscriminately, but this is not the case (Ben-Ami Bartal et al, 2014;Sato et al, 2015). It should be realized that a key difference among these various studies is the degree of distress.…”
Section: Prosociality: Helping Others In Distressmentioning
confidence: 96%
“…This was further attributed to social contact but again it poses the possibility that social contact was empathic in nature. Assuming that the social contact explanation was true, rats will be motivated to open restrainers and trap doors for distressed and non-distress cagemates indiscriminately, but this is not the case (Ben-Ami Bartal et al, 2014;Sato et al, 2015). It should be realized that a key difference among these various studies is the degree of distress.…”
Section: Prosociality: Helping Others In Distressmentioning
confidence: 96%
“…Rats will press a bar to lower another rat that is suspended in mid-air, which is interpreted as relieving the suspended animal's distress [118]. Rats helped distressed conspecifics that had been soaked with water, and chose to help the cage mate before obtaining a food reward ( [119] but see [120]). Moreover, rats prefer a mutual reward to a selfish reward [121] and this prosocial choice is motivated by food-seeking behaviour on the part of the other rat [122].…”
Section: (C) How Empathy Motivates Prosocial Behaviourmentioning
confidence: 99%
“…Though this result could be explained in a variety ways (e.g., the monkeys merely avoided doing something that caused an aversive stimulus), a not unreasonable interpretation is that the monkeys recognized and wished to avoid causing distress in others, suggesting some degree of sympathetic concern. Similar pro-social helping behaviours suggestive of empathy and sympathy have been documented in several species, including rats (Bartal et al, 2011;Sato et al, 2015), and chimpanzees, who have been shown to direct consoling behaviours towards losers after fights (de Waal, 1996;Fraser and Aureli, 2008) (2015), all of whom argue that at least a core subset of the psychological capacities that underlie human morality are far from uniquely human, but are rather things that we share with many social animals. Whatever differences may exist between their moral psychologies and moral systems and those of humans-none of these authors deny that there are such differences-should be seen as differences in the extent and sophistication of moral capacity.…”
mentioning
confidence: 57%
“…Though this result could be explained in a variety ways (e.g., the monkeys merely avoided doing something that caused an aversive stimulus), a not unreasonable interpretation is that the monkeys recognized and wished to avoid causing distress in others, suggesting some degree of sympathetic concern. Similar pro-social helping behaviours suggestive of empathy and sympathy have been documented in several species, including rats (Bartal et al, 2011;Sato et al, 2015), and chimpanzees, who have been shown to direct consoling behaviours towards losers after fights (de Waal, 1996;Fraser and Aureli, 2008) and display physiological signs of emotional arousal in response to images of violence or other chimpanzees displaying fearful or distressed facial expressions (reviewed by Rudolf von Rohr et al, 2011).…”
mentioning
confidence: 62%